Perancangan Sistem Informasi Pemasaran Berbasis Website Menggunakan CMS Pada CV. Dasacipta Sarana Medika - Jazuli, Ahmad Muhtar; , Ahmad Kholid Al Ghofari, ST. MT; , Ida Nursanti, ST., M.Eng.Sc (2016)
Marketing of products is one of the keys to maximizing the company's goal to generate profit. Without the marketing of the business or the business will not thrive. Marketing of each company is different. Some wear traditional systems and some are already using the modern technological developments. Seeing the current business developments, many technology-based marketing systems eg e-commerce website. Many businesses that had applied fields include fashion, electronics, health and so on. CV. Dasacipta Sarana Medika is one of the companies engaged in medical equipment, where to marketing is still through the store and sales. Through this research is intended to help CV. Dasacipta Sarana Medika in improving the competitiveness of product marketing. So expect the future can increase turnover and achieve maximum profit. In this study, the program used to create a website that is a Content Management System. The advantages of this program is the ease of manufacture and conversion information (update information) .From the results of e-commerce website creation contains several matters related to the company profile, how to order, product, health articles, customer testimonials, and confirmation of payment. The website provides a lot of convenience to visitors to get to know in detail about the company. With the e-commerce website will facilitate in marketing because it can expand the space for market share and even can be said that CV. Dasacipta Sarana Medika has a market share that is infinite.